GERAKAN ORANG TUA ASUH MENGATASI STUNTING - Aty, Yoani Maria V. B.; Herawanti, Elisabeth; Srinurwela, Trifonia; Selasa, Pius (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The incidence of stunting in Liliba Village, Oebobo Subdistrict, Kupang City, recorded 185 children experiencing stunting. There are 20 malnourished children and 70 undernourished children. Methods of stunting education and foster parent program to overcome stunting. Activities were carried out in May-August 2023. Activities were carried out in the Liliba sub-district of Kupang City. The activity results are Child A's nutritional status before the foster parent movement: body weight 11.3 kg, TB 82.6, and Lila 14.5. After 90 days of feeding, the weight was 12.4 kg, TB 85.8, and Lila 15.4. For Child J, the nutritional status of Child A before the foster parent movement was 9 kg, TB 75.3, and Lila 14.5. After 90 days of feeding, the weight was 9.1 kg, TB 78.1, and Lila 14.8. The results of educational activities are that parents' knowledge of Posyandu Jasmine 12 increased. The knowledge test results found that most participants had good knowledge before education, namely 50%. After education, 80% of family knowledge about stunting is excellent. Education about stunting is excellent for families to prevent stunting. The OTA2S program has a good impact on the nutritional status of stunted children.